Maxillary crossbite correction with a rapid palatal expansion followed by a corrective orthodontic treatment (Journal of Medical Sciences, 2022)
This case report presents the  orthodontic treatment of a Libyan girl  , aged 14 years 4 months with a Class lll  malocclusion with severe transverse maxillary deficiency ( anterior sever crowding ,canines buccally eruption  and posterior bilateral  crossbite)(Figure 1) and correction using Haas expander and fixed orthodontic appliance(Figure2). The treatment goals were to correct the posterior crossbite and anterior crowding and restore the normality of the dentition and occlusion. In phase I, the patient was treated with a modified Haas-type palatal expander, which provided a clinically significant palatal expansion and increased the maxillary arch perimeter with favourable conditions for orthodontic treatment with fixed appliances in phase II. A removable wraparound type appliance and a bonded lingual canine-to-canine retainer were used as retention. Although the literature has reported a high rate of relapse after palatal expansion, after 2 years 9 months of post treatment follow-up, the occlusal result was stable and no skeletal reversals could be detected.